Single-cell RNA sequencing in diffuse large B-cell lymphoma: tumor heterogeneity, microenvironment, resistance, and prognostic markers - Li, Linwei; Li, Qiwei; Niu, Rui; Sun, Wei; Liang, Hua (Frontiers in Oncology, 2025)
Diffuse large B-cell lymphoma (DLBCL) is a highly heterogeneous malignancy with challenges in treatment resistance and relapse. Single-cell RNA sequencing (scRNA-seq) has provided important insights into tumor heterogeneity, microenvironment interactions, resistance mechanisms, and prognostic biomarkers. This review summarizes key findings from scRNA-seq studies, which have deepened our understanding of DLBCL and contributed to the development of precision therapeutic strategies. Integrating scRNA-seq with spatial transcriptomics and single-cell multi-omics may further elucidate disease mechanisms and identify novel therapeutic targets, supporting the advancement of precision medicine in DLBCL.